Pd-Catalyzed imine cyclization: synthesis of antimalarial natural products aplidiopsamine A, marinoquinoline A, and their potential hybrid NCLite-M1 - Mahajan, Jyoti P.; Suryawanshi, Yogeshwar R.; Mhaske, Santosh B. (Organic Letters, 2012)
Palladium-catalyzed cyclization of imines has been developed to construct the extremely rare 3H-pyrrolo[2,3-c]quinoline ring system for diversity oriented first total synthesis of antimalarial marine natural product Aplidiopsamine A as well as synthesis of Marinoquinoline A and potential natural product hybrid NCLite-M1.